Clock-Controlled Regulation of the Acute Effects of Norepinephrine on Chick Pineal Melatonin Rhythms. (December 2015) - Li, Ye; Cassone, Vincent M.
The chicken pineal gland synthesizes and releases melatonin rhythmically in light/dark (LD) cycles, with high melatonin levels during the dark phase, and in constant darkness (DD) for several cycles before it gradually damps to arrhythmicity in DD. Daily administration of norepinephrine (NE) in vivo and in vitro prevents the damping and restores the melatonin rhythm. To investigate the role of the circadian clock on melatonin rhythm damping and of its restoration by NE, the effects of NE administration at different phases of the melatonin cycle revealed a robust rhythm in NE sensitivity in which NE efficacy in increasing melatonin amplitude peaked in late subjective night and early subjective day, suggesting a clock underlying NE sensitivity. However, NE itself had no effect on circadian phase or period of the melatonin rhythms. Transcriptional analyses indicated that even though the rhythm of melatonin output damped to arrhythmicity, messenger RNA (mRNA) encoding clock genes gper2, gper3, gBmal1, gclock, gcry1, and gcry2 ; enzymes associated with melatonin biosynthesis; and enzymes involved in cyclic nucleotide signaling remained robustly rhythmic. Of these, only gADCY1 (adenylate cyclase 1) and gPDE4D (cAMP-specific 3′, 5′-cyclic phosphodiesterase 4D) were affected by NE administration at the mRNA levels, and only ADCY1 was affected at the protein level. The data strongly suggest that damping of the melatonin rhythm in the chick pineal gland occurs at the posttranscriptional level and that a major role of the clock is to regulate pinealocytes' sensitivity to neuronal input from the brain.